Gamified Arabic Vocabulary Learning: Integrating Puzzle-Based Discovery Learning to Foster Learner Autonomy - Dzakiyatul Fikriyah; Inayah Inayah; Ruswan Ruswan; Lu'lu'ul Aini (South Sulawesi Education Development (SSED), 2026)
Existing studies rarely integrate puzzle-based educational games with the discovery learning model while simultaneously examining students’ learning independence as an affective outcome in Arabic vocabulary learning at the Junior Islamic School level. This study aims to examine, implement, and determine the effectiveness of Arabic vocabulary learning based on games that combine the use of puzzles with discovery learning in improving the learning independence of Junior Islamic School students in Kaliwungu, Kendal, Central Java. The method employed in this study was a quantitative approach with a pre-experimental design. The sample used was from class 8C Junior Islamic School NU 05 Sunan Katong, which consisted of 26 students. Data collection was conducted using observation techniques to measure student learning independence, interviews to gather supporting data, and tests to assess students' vocabulary comprehension. This study shows that integrating puzzle-based discovery learning in vocabulary learning is quite effective in improving student learning independence. The results of the analysis using SPSS showed a significance value of 0.000, which means that the value is <0.05, indicating that there is an effect of vocabulary learning through puzzle media and discovery learning on students' learning independence. The results of the N-Gain test showed a percentage value of 57.6066, which means that vocabulary learning through puzzle media and discovery learning is quite effective. Based on the results of observations, the measurement of student learning independence shows that most students fall into the category of being fairly independent. This means that game-based vocabulary learning through puzzles and discovery learning can encourage student independence in learning. These findings indicate that integrating puzzle-based discovery learning in vocabulary learning is needed for Arabic vocabulary learning in order to improve student learning independence.